Phenotypic characters and genetic variations of lurik peanuts (Arachis hypogaea L. var. lurikensis) with Inter Simple Sequence Repeat - Ikhsanudin Nur Rosyidi -; Budi Setiadi Daryono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rosyidi IN, Daryono BS. 2020. Phenotypic characters and genetic variations of lurik peanuts (Arachis hypogaea L. var. lurikensis) with Inter Simple Sequence Repeat. Biodiversitas 21: 629-635. Agriculture is a sector that supports national development, one of its commodities is peanut (Arachis hypogaea L.). The needs and demand for peanuts from the food industry sector increased throughout time. However, the current national production level is unable to fulfill the demand, so the number of peanut imports increased sharply.  Based on this condition, researches to improve peanuts production using Lurik peanuts should be held as a solution to fulfill the need for national consumption because lurik peanuts have a greater number of pods and seeds. This research was aimed to improve the quality and quantity of Lurik peanuts phenotype and analyze the successes through the variations and its molecular character. This research was done in May - July 2018 in Mutihan, Madurejo, Prambanan, Sleman, Yogyakarta and in the Laboratory of Genetics and Breeding of Faculty of Biology, Universitas Gadjah Mada (UGM), Yogyakarta, Indonesia. In this research, Lurik peanuts improvement was conducted by selection and induction with colchicine. The Data was collected qualitatively using Inter Simple Sequence Repeat (ISSR) with  ISSR 8, ISSR 9, UBC 825, UBC 841 primers and electrophoresis while the quantitative method was done using plant phenotype measurement and spectrophotometry, then followed by data analysis using one-way ANOVA and MVSP 3.1 program. The results of this research showed that the characters of Lurik peanuts were different from common peanuts such as in having higher plants, different numbers of seeds per pod, and pattern on the seed coat. These data were supported by the molecular results, with similarity index at 84% meaning that the Lurik peanuts and common peanuts are classified as one same species.